Qubbet el-Hawa, 2019. Issue 1 (June 2020) - Bommas, Martin; Khalifa, Eman
This field report covers the work of the Egypt Exploration Society and Macquarie University Joint Mission during the period of 2018 and 2019 at Qubbet el-Hawa (third to fifth field seasons). Excavations focused on the infrastructure of the Lower Necropolis (Sites B and C) and the discovery of the causeway of Tomb QH90 (Site E). A detailed analysis of the pottery found and archaeometrical results complement the report.